2008
DOI: 10.1128/jb.01781-07
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Acquisition Components of the Myxococcus xanthus Pho Regulon Are Regulated by both Phosphate Availability and Development

Abstract: In many organisms, phosphatase expression and phosphate (P) uptake are coordinately regulated by the Pho regulon. In Myxococcus xanthus P limitation initiates multicellular development, a process associated with changes in phosphatase expression. We sought here to characterize the link between P acquisition and development in this bacterium, an organism capable of preying upon other microorganisms as a sole nutrient source. M. xanthus seems to possess no significant internal P stores, as reducing the P concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Myxococcus xanthus wild-type strain DK1622 ( Kaiser, 1979 ) was used throughout, maintained on the rich medium DCY as described previously ( Whitworth et al, 2008 ), with incubation at 30°C. Low nutrient DCY/10 medium is DCY diluted to 10% v/v.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Myxococcus xanthus wild-type strain DK1622 ( Kaiser, 1979 ) was used throughout, maintained on the rich medium DCY as described previously ( Whitworth et al, 2008 ), with incubation at 30°C. Low nutrient DCY/10 medium is DCY diluted to 10% v/v.…”
Section: Methodsmentioning
confidence: 99%
“…Media were solidified with the addition of 1.5% agar. TM was used as a nutrient free medium for developmental assays ( Whitworth et al, 2008 ). E. coli strain TOP10 (Invitrogen) and B. megaterium (strain NCIMB 4821) were cultivated on LB ( Sambrook et al, 1989 ), solidified with 1.5% agar as required.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to the advent of genome sequencing, transcription was normally assayed in M. xanthus using northern blots or reporter genes. Typically, a promoterless lacZ gene would be cloned downstream of a promoter and introduced into the chromosome (typically at the attB site), with production of LacZ (measured by colorimetric assays) indicating transcriptional activity (e.g., [ 108 ]). Alternatively, a promoterless lacZ within the transposon Tn 5 lac allowed transcription to be assessed wherever a transposon had inserted into the chromosome [ 109 ].…”
Section: Myxobacterial Post-genomicsmentioning
confidence: 99%
“…xanthus (15), which have not been associated to any specific protein, so far. Hence, Whitworth et al (16) suggested that those phosphatase activities could be originated by specific PPs. Until now, only Pph1 has been characterized (17).…”
mentioning
confidence: 99%